The Impact of Employee Job Satisfaction on Dynamic Capability: The Mediating Role of Turnover Intention - Irawati, Marsha Ayunita; Hartarini, Yovita Mumpuni; Khayatun, Siti; Ahmi, Aidi (JDM (Jurnal Dinamika Manajemen), 2024)
This study aims to analyze three concepts, employee job satisfaction, dynamic capability, and turnover intention, without separating these three concepts by analyzing the effect of employee job satisfaction on dynamic capability and turnover intention as mediation. This research is correlative quantitative research with a cross-sectional approach for employees in Indonesia and uses SEM-PLS to analyze the data. The study results show that employee satisfaction has a negative and significant effect on turnover intention, and turnover intention has a negative and significant effect on dynamic capability; including the mediation variable in this study shows that turnover intention could mediate between employee satisfaction and dynamic capabilities. From the result, this research could be a starting point for developing flexible work program strategies and measures, as well as the implications in the changing business environment, especially in the digital era or situations that cause rapid changes quickly, like urgent situations or even uncertainty and contribute to further research discussing these three concepts.